A Sociological Analysis of Bhojpuri Jhoomar in Mauritius - Dawosing, Jayganesh (Advances in Social Sciences Research Journal, 2020)
To ensure a significant place among both the local and international Bhojpuri singers, the singers keep reproducing the cultural content of this type of Bhojpuri songs, called the ‘Jhoomar’ which literally means dancing in a circular motion. However, in this process of cultural evolution, the fear of either preserving the traditional or digressing from the latter will always be there. This paper deals with the sociological analysis of jhoomar songs of the present generation who create new lyrics in the Mauritian Bhojpuri songs. For entertainment purposes, some singers, at times, interpret the traditional forms in an expression of personal or group identity. The recent albums of certain of the artistes deal with contemporary issues, true to an articulation of social hierarchies, most notably race, gender and class. In correspondence to contemporary issues, a research question arises with the preservation of traditional form, how do the contemporary songs relate to broader social distinctions, especially class, race and gender? Fieldwork with local Bhojpuri singers has helped in understanding the significance of the study. This paper argues from a conceptual analysis of popular cultural significance of the study. The content of these jhoomar songs are relevant in culture and music of the 21st century, entailing fascinating issues of discussion.